The role of digital innovation in improving healthcare quality in extreme adversity: an interpretative phenomenological analysis study - Olivia Lounsbury; Lily Roberts; Natalia Kurek; Alexandra Shaw; Kelsey Flott; Saira Ghafur; Alain Labrique; Sheila Leatherman; Ara Darzi; Ana Luísa Neves (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background High quality is a necessary feature of healthcare delivery. Healthcare quality challenges are particularly present in conditions of extreme adversity, such as conflict settings or sustained humanitarian crises. Digital health technologies have recently emerged as an innovation to deliver care around the world in a variety of settings. However, there is little insight into how digital health technologies can be used to improve the quality of care where extreme adversity introduces unique challenges. This study aimed to identify how digital health technologies may be most impactful in improving the quality of care and evaluate opportunities for accelerated and meaningful digital innovation in adverse settings. # Methods A phenomenological approach (Interpretative Phenomenological Approach \[IPA\]), using semi-structured interviews, was adopted. Six individuals were interviewed in person based on their expertise in global health, international care delivery, and the application of digital health technologies to improve the quality of care in extreme adversity settings. The interviews were informed by a semi-structured topic guide with open-ended questions. The transcripts were compiled verbatim and were systematically examined by two authors, using the framework analysis method to extract themes and subthemes. # Results The participants identified several areas in which digital health technologies could be most impactful, which include engagement in care, continuity of care, workforce operations, and data collection. Opportunities for accelerated digital innovation include improving terminology, identity, ownership, and interoperability, identifying priority areas for digital innovation, developing tailored solutions, coordination and standardisation, and sustainability and resilience. # Conclusions These results suggest that there are conditions that favour or challenge the application of digital health technologies, even in specific areas in which they could be useful. A better understanding of the drivers and barriers to digitally driven quality improvement in settings of extreme adversity could inform international policies and optimisation strategies for the future.